Is the decline in neonatal mortality in northern Ghana, 1996–2012, associated with the decline in the age of BCG vaccination? An ecological study. Issue 12 (14th December 2018) - Welaga, Paul; Debpuur, Cornelius; Aaby, Peter; Hodgson, Abraham; Azongo, Daniel K; Benn, Christine S; Oduro, Abraham Rexford
Abstract : Objective: To examine the association between early Bacille Calmette-Guerin (BCG) vaccination and neonatal mortality in northern Ghana. Methods: This ecological study used vaccination and mortality data from the Navrongo Health and Demographic Surveillance System. First, we assessed and compared changes in neonatal mortality rates (NMRs) and median BCG vaccination age from 1996 to 2012. Second, we compared the changes in NMR and median BCG vaccination age from 2002 to 2012 by delivery place when data on delivery place were available. Results: Neonatal mortality rates declined from 46 to 12 per 1000 live births between 1996 and 2012 (trend test: p<0.001). Within the same period, median BCG vaccination age declined from 46 to 4 days (trend test: p<0.001). Among home deliveries, BCG vaccination age declined from 39 days in 2002 to 7 days in 2012 (trend test: p<0.001) and neonatal mortality declined by 24/1000 (trend test: p<0.001). Among health facility deliveries, BCG vaccination age was stable around 3 days from 2002 to 2012 (trend test: p=0.49) and neonatal mortality declined by 9/1000 (trend test: p=0.04). In a small study of children whose vaccination cards were inspected within the first 28 days of life, the HR for BCG-vaccinated compared with BCG-unvaccinated children was 0.55 (95% CI 0.12 to 2.40). Conclusion: The data support the hypothesis that early BCG vaccination may be associated with a decrease in neonatal mortality. However, as suggested by WHO, randomised control trials are required to address the question of whether there is indeed a causal association between early BCG vaccination and neonatal mortality.